Global Literary Studies Key Concepts - Roig-Sanz, Diana; Rotger, Neus (De Gruyter, 2022)
This book sets the grounds for Global Literary Studies as an emergent field. It innovatively looks at cross-border cultural phenomena through the concepts of space, scale, time, connectivity and agency, channeling the cross-fertilization of ideas across 4 lines: global translation flows, the global novel, global literary environments and global cinema. The book targets readers interested in a global critical approach in the humanities and beyond.